Young children’s difficulties in switching from rhythm production to temporal interval production (>1 s) - Bobin-Bègue, Anne; Droit-Volet, Sylvie; Provasi, Joëlle (Frontiers in Psychology, 2014)
This study examined the young children’s abilities to switch from rhythm production, with short 15 Inter-Taps Intervals (ITI), to temporal interval production, with long ITI (> 1 s), in a sensorimotor synchronization task. Children aged 3 and 5 years old were given 6 sessions of synchronization. In a control group, they had to synchronize their ITI to an Inter-Stimulus Interval (ISI) of 4 s. In the experimental group, they must progressively increase their ITI for one session to the next (from 0.4-s to 4.0-s ISI). Our results showed that the 5-year-olds produced longer ITI that the 3-year-olds in synchronization. However, the value of ITI in the 5-year-olds never exceeded 1.5 s, with more variable ITI in the control than in the experimental group. In addition, at 5 years, boys had more difficulties than girls in changing their tapping rhythm. These results suggest a temporal window in sensorimotor synchronization, beyond which the rhythm is lost and the synchronization becomes difficult.